Hate factory : a first-hand account of the 1980 riot at the penitentiary of New Mexico - Hirliman, Georgelle; Stone, W. G. (Lincoln, NE : iUniverse, 2005)
The terror lasted for thirty-six hours. When it was over, thirty-three inmates were dead, all at the hands of their fellow convicts. It was an outbreak of inmate violence unequaled in the annals of prison uprisings. It happened at the Penitentiary of New Mexico-Time magazine called it "the nation's most notorious prison."W.G. Stone was there. He witnessed the beatings, the stabbings, the rape, the torture."Tying the rope under his arms and around his chest, they strung him up on the basketball hoop for all to see. There he would hang for the rest of the riot During those hours of madness that were to follow, inmates would come in and hack at his dangling corpse with knives, beat it with pipes, mutilating it so totally that it was beyond recognition, a raw, bloody mass of flesh, by the time the uprising was over." The Hate Factory.--Cover
96592
Keywords: New Mexico State Penitentiary; Prison riots -- New Mexico -- Santa Fe; Prisons -- New Mexico -- Santa Fe; Mexican American prisoners